Episódio Queermuseu: reflexos do despreparo social em torno da Arte (Palíndromo, 2017)
This article aims to propose a reflection critical-reflexive on visual illiteracy in contemporary society considering that the lack of knowledge allowed the manipulation carried out by groups with political interests to lead to the closure of the exhibition Queermuseu. Documentary analysis and bibliographic review suggest that even among visitors and connoisseurs of exhibition spaces, there is a lack of knowledge about the role of art. In a transdisciplinary way, authors like Dondis, Cocchiarale, Eco and Hobsbawm base their research on concepts and information on contempo-rary art and on the process of constructing visual languages, which is often developing far from the formation of the public. Foucault, Marcuse, Berman, among others in the axis of cultural critique, support considerations about the political role of art and about the instruments of alienation that use the peoples ignorance.
Keywords: visual literacy; contemporary art; aesthetics; political; censorship